Implementasi dan Pengendalian Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) terhadap Kinerja K3 pada Proyek Konstruksi - Juliar, Eka; Adriadi, Adriadi; Siregar, Chandra Afriade (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2026)
Occupational Safety and Health (OSH) is a crucial aspect in construction projects, which are characterized by a high risk of workplace accidents. Improving OSH performance requires effective implementation of the Occupational Safety and Health Management System (OSHMS) as well as continuous control mechanisms. This study aims to analyze the effect of OSHMS implementation and control on OSH performance in construction projects. A quantitative approach was employed using a survey method by distributing questionnaires to respondents directly involved in construction project activities. The collected data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results indicate that OSHMS implementation has a positive and significant effect on OSH performance. In addition, OSHMS control also has a positive and significant effect on OSH performance, although its influence is lower than that of OSHMS implementation. These findings suggest that the implementation and control of OSHMS are complementary aspects in improving OSH performance in construction projects.